2013
DOI: 10.1002/cne.23306
|View full text |Cite
|
Sign up to set email alerts
|

In vivo characterization of a bigenic fluorescent mouse model of Alzheimer's disease with neurodegeneration

Abstract: The loss of cognitive function in Alzheimer’s disease (AD) patients is strongly correlated with the loss of neurons in various regions of the brain. We have created a new fluorescent bigenic mouse model of AD by crossing “H-line” yellow fluorescent protein (YFP) mice with the 5xFAD mouse model, which we call the 5XY mouse model. The 5xFAD mouse has been shown to have significant loss of L5 pyramidal neurons by 12 months of age. These neurons are transgenically labeled with YFP in the 5XY mouse, which enable lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 66 publications
(113 reference statements)
1
20
0
Order By: Relevance
“…Otherwise a decline in growth would be expected due to the ever-increasing surface area of β-amyloid plaques which requires a proportional increase in the amount of Aβ to maintain a constant linear growth rate. A comparison of plaque growth of the Tg2576 with the APPPS1 mouse model that was investigated by two other studies, using exactly the same methods and data analysis, supports this hypothetical assumption [16-20,31]. Although APPPS1 mice produce much more Aβ and accumulation starts much earlier than in Tg2576 mice [9,19,23,30] median plaque growth rates were about 0.3 μm/week in both mouse models [16-20,31].…”
Section: Discussionmentioning
confidence: 65%
“…Otherwise a decline in growth would be expected due to the ever-increasing surface area of β-amyloid plaques which requires a proportional increase in the amount of Aβ to maintain a constant linear growth rate. A comparison of plaque growth of the Tg2576 with the APPPS1 mouse model that was investigated by two other studies, using exactly the same methods and data analysis, supports this hypothetical assumption [16-20,31]. Although APPPS1 mice produce much more Aβ and accumulation starts much earlier than in Tg2576 mice [9,19,23,30] median plaque growth rates were about 0.3 μm/week in both mouse models [16-20,31].…”
Section: Discussionmentioning
confidence: 65%
“…Specifically, we detected a decrease in spontaneous miniature excitatory post-synaptic currents (mEPSCs) frequency and amplitude, higher threshold for firing of action potentials, a decrease in spike half-width duration and a decrease in synaptic weight following spike-timing dependent plasticity (STDP). We have recently shown that spine density and morphology on layer 5 neurons in young 5xFAD mice are unchaged from age-matched controls (Crowe and Ellis-Davies, 2013b), our data suggest that these cells in the 5xFAD mouse model undergo synaptic deficits at an early time point, before any overt structural dystrophy (Crowe and Ellis-Davies 2013a), and that such synaptic failure, with co-temporal biochemical changes(Eimer and Vassar, 2013), may be an early step in neuronal loss.…”
Section: Introductionmentioning
confidence: 62%
“…More recent quantitative analyses of such decay revealed that between 25%(Eimer and Vassar, 2013) to 38%(Jawhar et al ., 2012) of layer 5 neurons are lost by 12 months of age. Furthermore, we have shown recently by high-resolution imaging in vivo and in vitro that dendritic spines are stable at 4 months of age, whilst axons are starting to show signs of dystrophy at this time(Crowe and Ellis-Davies, 2013a). Since the 5xFAD mouse is one of the few amyloid transgenic mice to exhibit profound structural decay, it has attracted considerable interest from several research groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BACE1 elevation appears to occur in the brain from a fairly early age among several plaque-forming transgenic AD models examined so far, including Tg2576, 2XFAD, 5XFAD, and 3xTgAD [10,11,35-37,39,66,67]. Importantly, the onset and evolution of typical neuritic plaques in the brain and spinal cord correlate with a progressive axon terminal pathology associated with BACE1 overexpression.…”
Section: Introductionmentioning
confidence: 99%